2022
DOI: 10.1177/11206721221116013
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal recombinant tPA before vitrectomy for diabetic tractional retinal detachment: A randomized controlled trial

Abstract: Purpose To investigate the effect of intravitreal recombinant tissue plasminogen activator (rt-PA) injection before vitrectomy on surgical facility and outcome in diabetic tractional retinal detachments (TRD). Methods Prospective, randomized, interventional clinical trial. A total of 38 eyes with diabetic TRD were candidates for vitrectomy. Patients were randomized 1:1 to receive intravitreal rt-PA, five to seven days before vitrectomy or no injection. Intraoperative surgical facility and anatomic success at m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The authors speculated that the possible reasons for failure could be the variability of the action of t-PA, conditional response on the presence of plasminogen, insufficient t-PA dose, and short time interval between the injection and surgery (8) . Recently, Falavarjani et al showed that t-PA injection 5-7 days before surgery is beneficial in decreasing the number of iatrogenic retinal break formations and surgery time in cases with diabetic tractional retinal detachment (11) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors speculated that the possible reasons for failure could be the variability of the action of t-PA, conditional response on the presence of plasminogen, insufficient t-PA dose, and short time interval between the injection and surgery (8) . Recently, Falavarjani et al showed that t-PA injection 5-7 days before surgery is beneficial in decreasing the number of iatrogenic retinal break formations and surgery time in cases with diabetic tractional retinal detachment (11) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we used 50 µg of t-PA, which was greater than the 25 µg used in previous studies, to generate more plasmin. Falavarjani et al also used 50 µg of t-PA and injected t-PA 5-7 days preoperatively (11) .…”
Section: Discussionmentioning
confidence: 99%